2011
DOI: 10.1107/s160053681103580x
|View full text |Cite
|
Sign up to set email alerts
|

4-[Bis(4-fluorophenyl)methyl]piperazin-1-ium picrate

Abstract: The title compound {systematic name: 4-[bis(4-fluorophenyl)methyl]piperazin-1-ium 2,4,6-tri­nitro­phenolate}, C17H19F2N2 +·C6H2N3O7 −, is the picrate salt of a piperazine-supported amine bearing a benzhydryl substituent on one of its N atoms. During co-crystallisation, protonation took place on the N atom of the secondary amine functionality. The non-aromatic six-membered heterocycle adopts a chair conformation. In the crystal, N—H⋯O hydrogen bonds as well as C—H⋯O contacts connect the components into a three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…The crystal structures of 4-[bis(4-fluorophenyl)methyl]piperazin-1-ium 2-(2-phenylethyl) benzoate (Betz et al, 2011a), 4-[bis(4-fluorophenyl)methyl]piperazin-1-ium picrate (Betz et al, 2011b) (Dai et al, 2012) have been reported. In the course of our studies on the salts of piperazines and in view of the importance of piperazines, this paper reports the crystal and molecular structure of the title compound, C 19 H 20 F 2 N 2 O, (I), which was accidentally obtained by the reaction of 4,4′-difluorobenzhydryl piperazine and acetyl salicylic acid.…”
Section: -{4-[bismentioning
confidence: 99%
“…The crystal structures of 4-[bis(4-fluorophenyl)methyl]piperazin-1-ium 2-(2-phenylethyl) benzoate (Betz et al, 2011a), 4-[bis(4-fluorophenyl)methyl]piperazin-1-ium picrate (Betz et al, 2011b) (Dai et al, 2012) have been reported. In the course of our studies on the salts of piperazines and in view of the importance of piperazines, this paper reports the crystal and molecular structure of the title compound, C 19 H 20 F 2 N 2 O, (I), which was accidentally obtained by the reaction of 4,4′-difluorobenzhydryl piperazine and acetyl salicylic acid.…”
Section: -{4-[bismentioning
confidence: 99%
“…Supplementary data and figures for this paper are available from the IUCr electronic archives (Reference: BT5853). phenyl)methyl]piperazin-1-ium 2-(2-phenylethyl) benzoate (Betz et al, 2011a), 4-[bis(4-fluorophenyl)methyl]piperazin-1-ium picrate (Betz et al, 2011b) and cyclobenzaprinium salicylate (Fun et al, 2011) have been reported. In the course of our studies on the salts of piperazines and in view of the importance of piperazines, we now report the crystal and molecular structure of the title compound.…”
Section: Data Collectionmentioning
confidence: 99%
“…For the biological activity of piperazines, see: Brockunier et al (2004); Bogatcheva et al (2006). For related structures, see: Anilkumar et al (2005); Betz et al (2011); Fun et al (2011); Jasinski et al (2010Jasinski et al ( , 2011; Dutkiewicz et al (2011). For graphset analysis of hydrogen bonds, see: Etter et al (1990); Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…The crystal structures of some related compounds, viz., 2-(2phenylethyl)benzoic acid (Anilkumar et al, 2005), levocetirizinium dipicrate (Jasinski et al, 2010), cinnarizinium dipicrate (Jasinski et al, 2011), 1-methylpiperazine-1,4-diium dipicrate (Dutkiewicz et al, 2011) and 4-(4-chlorophenyl)-4-hydroxypipe ridinium 2-(2-phenylethyl)benzoate (Fun et al, 2011) have been reported. Recently, we have reported the crystal structure of 4-[bis(4-fluorophenyl) methyl]piperazin-1-ium picrate (Betz et al, 2011). In the course of our studies on the salts of piperazines and in view of the importance of piperazines, the paper reports the crystal and molecular structure of the title salt.…”
Section: S1 Commentmentioning
confidence: 99%